Stability and genetic insights of the co-existence of blaCTX-M-65, blaOXA-1, and mcr-1.1 harboring conjugative IncI2 plasmid isolated from a clinical extensively-drug resistant Escherichia coli ST744 in Shanghai - Feng, Jun; Wu, Huanyu; Zhuang, Yuan; Luo, Jiayuan; Chen, Yong; Wu, Yitong; Fei, Jiayi; Shen, Qi; Yuan, Zhengan; Chen, Min (Frontiers in Public Health, 2023)
Background Co-existence of colistin, β-lactam and carbapenem in multidrug-resistant Enterobacteriaceae isolates poses a serious threat to public health. In this study, we investigated and characterized the co-occurrence of blaCTX-M-65, blaOXA-1, and mcr-1.1 strain isolated from a clinical extensively-drug-resistant Escherichia coli ST744 in Shanghai. Methods Antimicrobial susceptibility test was carried out by agar dilution methods. Whole genome sequencing was conducted, and resistance genes, and sequence types of colistin in E. coli isolates were analyzed. Plasmid stability and amino acid mutations were assessed in E. coli isolates. Results A colistin resistant E. coli ST744, named ECPX221, was identified out of 145 fecal samples collected. The strain carries a 60,168 IncI2 plasmid with the mcr-1.1 gene. The strain also has blaCTX-M-65, blaOXA-1, dfrA14, qnrS1, cmlA5, arr2, ampC, aph(4)-Ia, sul1, and aadA5 resistance genes. The plasmid pECPX221 was capable of conjugation with an efficiency of 2.6 × 10−2. Notably, 45% of the transconjugants were determined as mcr-1.1-harboring in the colistin-free environment after 60 generation of passage. No mutations occurred in pmrB, mgrB, and phoPQ gene in the mcr-1.1-harboring transconjugants. Bioinformatic analysis indicated pECPX221 shared highly similar backbone with the previously reported mcr-1.1-harboring pAH62-1, pMFDS1339.1, pSCZE4, and p2018-10-2CC. Furthermore, sequencing and phylogenetic analyses revealed a similarity between other MCR-1-homolog proteins, indicating that ECPX221 was colistin resistant. Conclusion The stable transferable mcr-1.1-harboring plasmid found in the E. coli ST744 strain indicated the high risk to disseminate the extensively-drug-resistance phenotype among Enterobacteriaceae.